Impact of Educational Intervention on Mothers Empowerment about Proper Nutrition among Infants under 2 years of age Covered By Health Homes of District 18 of Tehran Municipality - fatemeh moradi; tohid babazade; nayer zebae (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Due to the importance of breastfeeding and eating habits formed and beginning complementary feeding in the first two years of life, this period is the most important period for child growth and development. The purpose of this study was to determine the effect of education on empowering mothers about correct nutrition among infants less than two years in the health homes of district 18 of Tehran Municipality. Methods: This study was a quasi-experimental study. Samples were selected using multi-stage sampling Researcher-made questionnaire was used to collect data. After confirming the validity and reliability (α= 0.82), control and intervention groups selected and data were collected. Then three educational sessions were held using educational tools such as boards and educational methods questions and answers to the intervention group. Three months after the intervention data were collected and analyzed using of descriptive statistics and independent T and paired T.Results: Before the intervention, the mean scores, among intervention group, of knowledge 13.30, attitude 24.99 and behavior 13.97 and after the intervention increased to 14.92, 27.45 and 14.39, respectively. Also mean score of knowledge, attitude and behavior of the control group before the intervention were 13.2, 23.70 and 13.59 and after the intervention were 13.24, 24.47 and 13.45, respectively. Conclusion: According to the result of this study, education can be used as an effective tool in the promotion of knowledge, attitude and practice of child nutrition. Article type: Research article.